Heparin inhibits cellular invasion by SARS-CoV-2: structural dependence of the interaction of the surface protein (spike) S1 receptor binding domain with heparin - Mycroft-West, Courtney J.; Su, Dunhao; Pagani, Isabel; Rudd, Timothy R.; Elli, Stefano; Guimond, Scott E.; Miller, Gavin; Meneghetti, Maria C. Z.; Nader, Helena B.; Li, Yong; Nunes, Quentin M.; Procter, Patricia; et al. (bioRxiv, 2020)
The dependence of the host on the interaction of hundreds of extracellular proteins with the cell surface glycosaminoglycan heparan sulphate (HS) for the regulation of homeostasis is exploited by many microbial pathogens as a means of adherence and invasion. The closely related polysaccharide heparin, the widely used anticoagulant drug, which is structurally similar to HS and is a common experimental proxy, can be expected to mimic the properties of HS. Heparin prevents infection by a range of viruses if added exogenously, including S-associated coronavirus strain HSR1. Heparin prevents infection by a range of viruses if added exogenously, including S-associated coronavirus strain HSR1. Here, we show that the addition of heparin to Vero cells between 6.25 - 200 μg.ml−1, which spans the concentration of heparin in therapeutic use, and inhibits invasion by SARS-CoV-2 at between 44 and 80%. We also demonstrate that heparin binds to the Spike (S1) protein receptor binding domain and induces a conformational change, illustrated by surface plasmon resonance and circular dichroism spectroscopy studies. The structural features of heparin on which this interaction depends were investigated using a library of heparin derivatives and size-defined fragments. Binding is more strongly dependent on the presence of 2-O or 6-O sulphation, and the consequent conformational consequences in the heparin structure, than on N-sulphation. A hexasaccharide is required for conformational changes to be induced in the secondary structure that are comparable to those that arise from heparin binding. Enoxaparin, a low molecular weight clinical anticoagulant, also binds the S1 RBD protein and induces conformational change. These findings have implications for the rapid development of a first-line therapeutic by repurposing heparin as well as for next-generation, tailor-made, GAG-based antiviral agents against SARS-CoV-2 and other members of the Coronaviridae.